Zika-prevention Knowledge among Hispanic Women Living in Puerto Rico: A Cross-sectional Study - Medina-Cucurella, Evaristo; Acevedo-Canabal, Jorge; De León-Arbucias, Jeidiel; Martínez-Torres, Rafael; Cruzado-Ramos, Gustavo; Romaguera, Josefina (Puerto Rico Health Sciences Journal, 2018)
Objective: To describe the level of knowledge about Zika virus exposure, symptoms, complications, and transmission prevention in Hispanic women living in Puerto Rico. Methods: A sample of 168 women aged 21 to 64 at the general community, consented to complete a self-administered questionnaire of 112 questions from October 2016 to July 2017. Results: A univariate analysis showed that the participating women recognized that the Zika virus was transmitted through mosquito bites (95.2%), sexual intercourse (78.0%), and from a mother to her fetus (41.1%); participants also believed that other, incorrect, routes of transmission were plausible. Regarding their knowledge of Zika infection prevention, the participants’ correct answers included the following: using mosquito repellent (94.1%), eliminating standing water (83.9%), and using condoms (83.3%). When asked about fetal risks associated with Zika, they believed that the fetus would not develop normally (75.6%), would be born with a disability (69.6%), or would experience nervous system problems (54.2%). Only 22.6% of the participants had taken precautions to prevent pregnancy during the Zika outbreak, of which 65.8% reported that they had used condoms during all sexual relationships. Conclusion: There is a need to educate the general population about the Zika virus to reduce the misconceptions about disease prevention and transmission as well as about the complications associated with Zika during pregnancy. Awareness efforts should emphasize the prevention of infections during pregnancy and the use of available contraceptive methods.